(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
A Filed experiment was carried out at the center of the guiding and training agriculture AL-Mahnawia – Babylon during spring season 2015 and autumn season at the same year growing six lines (OH40،ZP707،ZP670،IK8،R153 and Dk(to study and evaluation these lines and its hybrids at autumn season 2015 for traits : leaf area ,number of ears ,number of grain .ears-1 , grain yield ,total grain yield, by plating at (20,25,30)cm .by using RCBD design for three replicates. The results showed that significant difference among the genotypes, plant density and the interaction among them. The fifth inbred was superior for all study traits leaf area, number of ears, number of grains.ear-1 , grain yield, total grain yield it gives 3466 cm2, 1.10 ear.plant-1. 393.36 grans .ear-1 ,125.45 . gr, plant -1 ,10.6ton.ha-1 at 25 cm it was superior on all the study inbreds by giving a high value of these traits .on another hand the hybrid (R153× IK8 )gave a high range of all study traits 5439 cm2,1.25 aer.plant-1.635.30 gr. Plant-1 10.6 ton. ha-1. The line R153 and the hybrid( R153× IK8 (gave the best interaction.